The Relationship of Physical Fitness and Science Learning Outcomes of Students - Mukholid, Agus (Jurnal Penelitian Pendidikan IPA, 2023)
This research raises the issue of whether there is a relationship between physical fitness and science learning outcomes at SMP Negeri 8 Bekasi for the 2022/2023 academic year. This research aims to determine the relationship between physical fitness and the science learning outcomes of students at SMP Negeri 8 Bekasi for the 2022/2023 academic year. This research uses descriptive research methods. The population in this study was 180 class IX students of SMP Negeri 8 Bekasi for the 2022/2023 class. Then 35 people were taken using a random sampling technique (20% of the total population). Physical fitness data collection techniques using physical fitness tests and science learning outcomes by taking documentation data in the form of student report cards. Data processing is carried out using the correlation formula. The results of the research show that there is a significant relationship between physical fitness and science learning outcomes for students of IX SMP Negeri 8 Bekasi in the 2012/2013 academic year with (r = 0.70). Physical fitness contributes 49.7% to science learning outcomes at SMP Negeri 8 Bekasi.